BLOCK-MODULE METHOD FOR DESIGNING RESIDENTIAL BUILDINGS OF RURAL AREA IN HAINAN PROVINCE - Fan Jinyong (Наука и техника)
The most widely-spread type of a rural dwelling-house in the Hainan province presenting the most populated part of China is a «Siheyuan» country estate. Its lay-out structure contains an open internal courtyard and all the buildings are practically always located symmetrically relative to a central axis on the sides of the courtyard. The Siheyuan composition permits to divide it in elements which are convenient for a separate construction and for being connected in multi-element block-schemes.  In this connection the designing block-module method can be recommended as the most prospective one for improvement of the methodology for designing rural dwelling houses. Their large-scale construction on the valley territories of the Hainan province is planned by the leadership of the People’s Republic of China.